Wheat Ammonium Transporter (AMT) Gene Family: Diversity and Possible Role in Host–Pathogen Interaction with Stem Rust - Li, Tianya; Liao, Kai; Xu, Xiaofeng; Gao, Yue; Wang, Ziyuan; Zhu, Xiaofeng; Jia, Baolei; Xuan, Yuanhu (Frontiers in Plant Science, 2017)
Ammonium transporter (AMT) proteins have been reported in many plants, but no comprehensive analysis was performed in wheat. In this study, we identified 23 AMT members (hereafter TaAMTs) using a protein homology search in wheat genome. Tissue specific expression analysis showed that TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a were relatively more highly expressed in comparison with other TaAMTs. TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a-GFP were localized in the plasma membrane in tobacco leaves, and TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a successfully complemented a yeast 31019b strain in which ammonium uptake was deficient. In addition, the expression of TaAMT1;1b in an Arabidopsis AMT quadruple mutant (qko) successfully restored NH4+ uptake ability. Resupply of NH4+ rapidly increased cellular NH4+ contents and suppressed expression of TaAMT1;3a, but not of TaAMT;1;1a and TaAMT1;1b expressions. Expression of TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a was not changed in leaves after NH4+ resupply. In contrast, N deprivation induced TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a gene expressions in the roots and leaves. Expression analysis in the leaves of the stem rust-susceptible wheat line “Little Club” and the rust-tolerant strain “Mini 2761” revealed that TaAMT1;1a, TaAMT1;1b, and TaAMT1;3a were specifically induced in the former but not in the latter. Rust-susceptible wheat plants grown under N free conditions exhibited a lower disease index than plants grown with NH4+ as the sole nitrogen source in the medium after infection with Puccinia graminis f. sp. tritici, suggesting that NH4+ and its transport may facilitate the infection of wheat stem rust disease. Our findings may be important for understanding the potential function TaAMTs in wheat plants.